2015
DOI: 10.1017/s0267190514000191
|View full text |Cite
|
Sign up to set email alerts
|

Identity and a Model of Investment in Applied Linguistics

Abstract: This article locates Norton's foundational work on identity and investment within the social turn of applied linguistics. It discusses its historical impetus and theoretical anchors, and it illustrates how these ideas have been taken up in recent scholarship. In response to the demands of the new world order, spurred by technology and characterized by mobility, it proposes a comprehensive model of investment, which occurs at the intersection of identity, ideology, and capital. The model recognizes that the spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
577
1
32

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 712 publications
(621 citation statements)
references
References 70 publications
11
577
1
32
Order By: Relevance
“…We have identified nine research tasks that may help scholars address three broad research questions that focus on the relationship between language learners and teachers within particular institutional and transnational contexts. These research tasks, which are illustrative rather than exhaustive, range from the application of Darvin & Norton's (2015) model of investment to study intersectionality, to the examination of social media platforms to better understand lingua franca speakers. We have introduced each research task with a key study in the field, and bookended the article with a discussion of contemporary social theory relevant to identity in the first section of the article, and methodology innovations in applied linguistics in the final section.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have identified nine research tasks that may help scholars address three broad research questions that focus on the relationship between language learners and teachers within particular institutional and transnational contexts. These research tasks, which are illustrative rather than exhaustive, range from the application of Darvin & Norton's (2015) model of investment to study intersectionality, to the examination of social media platforms to better understand lingua franca speakers. We have introduced each research task with a key study in the field, and bookended the article with a discussion of contemporary social theory relevant to identity in the first section of the article, and methodology innovations in applied linguistics in the final section.…”
Section: Resultsmentioning
confidence: 99%
“…During this time, innovations in digital technology and increasing transnational connection have shifted our understanding of time, space, and our place in the world (Darvin & Norton 2015). Using social media, transnational learners can now connect the past, present, and future in unprecedented ways, and access to conversations is negotiable both on-and offline.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is important to note that this study did not directly probe the impact of L2 testing practices on language learners' desire or willingness to commit to, or invest in, language learning over time (Darvin and Norton, 2015;Norton, 2013). Despite these limitations, this research revealed significant patterns in the relationship between young adolescents' L2 motivation and their L2 testing experience; findings we hope will spur greater interest and investigation.…”
Section: Resultsmentioning
confidence: 99%
“…For example, it could be argued that students who prepared more for L2 tests may simply have valued the activity more, anticipated a greater chance of success, and were thus more highly motivated. However, this simplistic interpretation would fail to shed much light on how language learner thought and behaviour is influenced by the wider sociocultural environment impinging on all language learners, and how motivational behaviour is shaped over time and space, a longitudinal process captured more accurately by the notion of "investment" (see Darvin and Norton, 2015;Norton, 2013).…”
Section: Research Question #2b: L2 Test Preparation Time and L2 Motivmentioning
confidence: 99%
“…Discussions around the power of technology to change more than the way we do but also the way we are, are only beginning (Darvin & Norton, 2015). Connections that need to be drawn and pursued between enriched social cultural contexts, social networking technologies and opportunities for identity construction leading to self-directed learners have been relatively unexplored.…”
Section: Literature Reviewmentioning
confidence: 99%